Controlled Release Urea as a Nitrogen Source for Spring Wheat in Western Canada: Yield, Grain N Content, and N Use Efficiency - Lenz Haderlein; T.L. Jensen; R.E. Dowbenko; A.D. Blaylock (The Scientific World Journal)
Controlled release nitrogen (N) fertilizers have been commonly used in horticultural applications such as turf grasses and container-grown woody perennials. Agrium, a major N manufacturer in North and South America, is developing a low-cost controlled release urea (CRU) product for use in field crops such as grain corn, canola, wheat, and other small grain cereals. From 1998 to 2000, 11 field trials were conducted across western Canada to determine if seed-placed CRU could maintain crop yields and increase grain N and N use efficiency when compared to the practice of side-banding of urea N fertilizer. CRU was designed to release timely and adequate, but not excessive, amounts of N to the crop. Crop uptake of N from seed-placed CRU was sufficient to provide yields similar to those of side-banded urea N. Grain N concentrations of the CRU treatments were higher, on average, than those from side-banded urea, resulting in 4.2% higher N use efficiency across the entire N application range from 25 to 100 kg ha-1. Higher levels of removal of N in grain from CRU compared to side-banded urea can result in less residual N remaining in the soil, and limit the possibility of N losses due to denitrification and leaching.